2017
DOI: 10.1021/acs.orglett.7b00836
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Carbocyclic Propellanes

Abstract: A modular synthesis of functionalized carbocyclic propellanes was developed. Formation of the first of two quaternary bridgehead centers has been achieved by desymmetrization of prostereogenic ketones by either Hajos-Parrish-Eder-Sauer-Wiechert-type processes or Werner's catalytic asymmetric Wittig reaction. The obtained bicyclic enones were subjected to conjugate additions upon which the remaining ring was formed by olefin metathesis. All bridges are amenable to further derivatization, which renders those com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 29 publications
0
32
0
2
Order By: Relevance
“…In a recent study, Christmann and co-workers reported a modular synthesis of functionalized propellanes, including the [3.3.3] propellanedione 252 (Scheme 37). 134 In this strategy, prochiral triketones like 247 were catalytically desymmetrized to access bicylic structures such as 249. Then, diastereoselective addition of alkenyl-cuprates gave access to dienic structures such as 250, which were cyclized to propellanes using olen metathesis.…”
Section: Radical Cyclizationsmentioning
confidence: 99%
“…In a recent study, Christmann and co-workers reported a modular synthesis of functionalized propellanes, including the [3.3.3] propellanedione 252 (Scheme 37). 134 In this strategy, prochiral triketones like 247 were catalytically desymmetrized to access bicylic structures such as 249. Then, diastereoselective addition of alkenyl-cuprates gave access to dienic structures such as 250, which were cyclized to propellanes using olen metathesis.…”
Section: Radical Cyclizationsmentioning
confidence: 99%
“…This intermediate can be further simplified to propellenedione 6 . Using our recently developed strategy for the synthesis of 6 and other functionalized [a.b.c]propellanes from prochiral triketones such as 7 , we set out to demonstrate the utility of 6 in the synthesis of dichrocephones A and B.…”
Section: Figurementioning
confidence: 99%
“…Our synthesis began with the silver‐catalyzed bromination of alkyne 8 , which is readily available on a decagram scale from cyclopentane‐1,3‐dione (Scheme ). Changing the bromonium source from NBS to the corresponding nitrophthalimide derivative was critical to allow us to lower the amount of silver(I)nitrate from previously stoichiometric amounts to 5 mol %, affording bromoalkyne 9 in 91 % yield. Alkyne hydration proceeded smoothly using 4 mol % of PPh 3 AuNTf 2 , giving α‐bromoketone 7 in 88 % yield.…”
Section: Figurementioning
confidence: 99%
“…Die enantioselektive Synthese der Dichrocephone, Triquinan-Sesquiterpene mit einem Bicyclo-[3.3.3]undecan-Motiv, von Christmann, der ebenfalls eine allgemeine Strategie zur Synthese komplexer Propellane durch enantioselektive Wittig-Reaktion oder Organokatalyse und Ringschlussmetathese entwickelte, ist hier beispielhaft. [6] Einer der komplexesten Naturstoffe, die ein Propellan beinhalten, ist das Canataxpropellan (1, Abbildung 1), ein 2007 aus den Blättern der kanadischen Eibe, Taxus cana-densis, isoliertes 3,11:4,12:14,20-Tricyclotaxan. [7] Die Synthese von Taxanen und deren umgelagerter Derivate beschäftigt die synthetisch-organischen Chemiker schon seit geraumer Zeit.…”
unclassified